Pelatihan Sambung Pucuk Tanaman Manggis di Kecamatan Langgam - Yudia Azmi; Resy Nirawati; Zurrahmi Wirda; Luhgiatno Luhgiatno; Rauza Sukma Rita (Borneo Research and Educatin Center, 2023)
Mangosteen is a tropical fruit that grows in Langgam District, Pelalawan District, Riau Province. However, mangosteen is still difficult to consume because it is slow to bear fruit. One of the steps to speed up fruiting mangosteen plants is propagation by grafting. This community service activity aims to train the community in developing new ways to make mangosteen plants bear fruit quickly. The method used in this community service activity includes the provision of material/theory, demonstrations and direct practice for grafting mangosteen plants. The training participants in the community service program activities exceeded the target with the planned number of 10 participants being attended by 15 participants and 5 students. The participants stated that this activity was very useful and a new experience. This community service activity went well and was even specifically asked to provide training to farmer groups in the Segati area for further service